Use of the Kahoot Application in an Effort to Increase Student Motivation - Nur Indah Rismawati (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
The purpose of this study was to increase the motivation of students in grade 1 SD Negeri Pasekaran 02. This research was a classroom action research (CAR) which was carried out in three cycles, each cycle consisting of planning, implementation, observation, and reflection stages. The subjects of this study were students in grade 1 SD Negeri Pasekaran 02 in the 2020/2021 school year, totaling 26 students. Data collection techniques using observation and questionnaires. Data analysis includes data reduction, data presentation, and drawing conclusions. Research shows that the use of the kahoot application can increase the learning motivation of grade 1 students of SD Negeri Pasekaran 02 in the 2020/2021 school year as evidenced by the percentage of student responses in cycle I there are 12 students with high motivation with a percentage of 46%, 8 students with moderate motivation with a percentage of 31%, and 6 students whose motivation was low with a percentage of 23% while in cycle II there was an increase, namely there were 23 students who had high motivation with a percentage of 88%, and 3 students whose motivation was moderate with a percentage of 12% and in cycle III also experienced an increase, namely there were 25 students with high motivation with a percentage of 96%, and 1 student whose motivation was moderate with a percentage of 4%.